The efficiency challenge of nitride light‐emitting diodes for lighting. Issue 5 (13th March 2015) - Weisbuch, Claude; Piccardo, Marco; Martinelli, Lucio; Iveland, Justin; Peretti, Jacques; Speck, James S.
<x xml:space="preserve">Abstract</x> We discuss the challenges of light‐emitting diodes in view of their application to solid‐state lighting. The requirement is to at least displace the quite efficient fluorescent, sodium, and high intensity discharge lamps used today in the main energy consuming lighting sectors, industrial, commercial and outdoors, with more efficient and better light quality lamps. We show that both from the point of view of cost of ownership and carbon emissions reduction, the relevant metric is efficiency, more than the cost of lumens. Then, progress from present performance requires identification of the loss mechanisms in light emission from LEDs, and solutions competing with mainstream c‐plane LEDS grown on sapphire need to be on par with these. Special attention is devoted to a discussion of the efficiency droop mechanisms, and of a recent direct measurement of Auger generated electrons which appear to be responsible for droop.